Massiveness of Exceptional Sets of Multi-Term Asymptotic Representations of Subharmonic Functions in the Plane - Agranovich, P. (Журнал математичної фізики, аналізу, геометрії, 2006)
It was investigated the massiveness of exceptional sets that arise in multiterm asymptotic representations of subharmonic functions. It was shown that such exceptional sets be any $C_{0,1+γ}$-sets where $γ \in [0,1]$. This fact distinguishes the case of $n$-term asymptotic from the case of functions of completely regular growth. Mathematics Subject Classification: 30D20, 30D35, 31A05, 31A10.